2021
DOI: 10.1021/acsabm.0c01243
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Nanotopography on the Microfibers of 3D-Printed PCL Scaffolds to Modulate Cellular Responses and Establish an In Vitro Tumor Model

Abstract: Scaffold-based three-dimensional (3D) cell culture systems have gained increased interest in cell biology, tissue engineering, and drug screening fields as a replacement of twodimensional (2D) monolayer cell culture and as a way to provide biomimetic extracellular matrix environments. In this study, microscale fibrous scaffolds were fabricated via electrohydrodynamic printing, and nanoscale features were created on the fiber surface by simply leaching gliadin of poly(ε-caprolactone) (PCL)/ gliadin composites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…2 This differs from their natural growth manner where spherical macrophages are supported by neighboring cells and ECM 27 and thus lead to false positive anti-inflammatory compound screening results. 7,8 EHDJ is a highly precisely controlled 3D printing technology, and the EHDJ-printed scaffolds have been applied to culture various cell lines, for example, NIH/3T3 and A549 cells on PCL and PCL/zein scaffolds, 11,26 murine macrophages on NIR-II-dye-containing PCL scaffolds, 28 and human macrophages and PC12 cells on PCL scaffolds. 22,29 In all these studies, cells showed behaviors different from traditional in vitro cells and demonstrated their potential of biomimetic structural organization and application in tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 This differs from their natural growth manner where spherical macrophages are supported by neighboring cells and ECM 27 and thus lead to false positive anti-inflammatory compound screening results. 7,8 EHDJ is a highly precisely controlled 3D printing technology, and the EHDJ-printed scaffolds have been applied to culture various cell lines, for example, NIH/3T3 and A549 cells on PCL and PCL/zein scaffolds, 11,26 murine macrophages on NIR-II-dye-containing PCL scaffolds, 28 and human macrophages and PC12 cells on PCL scaffolds. 22,29 In all these studies, cells showed behaviors different from traditional in vitro cells and demonstrated their potential of biomimetic structural organization and application in tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Among various techniques, electrohydrodynamic jetting (EHDJ) is an emerging technology that precisely controls pore size, geometry, and fiber diameter of scaffolds. 11 It combines the working principles of the additive manufacturing technique and the electrospinning technique. On the one hand, it applies a stage motion and layer-by-layer stacking principle in additive manufacturing to fabricate scaffolds with certain pattern and 3D structure, which is also the reason for it to belong to 3D printing approaches; on the other hand, it applies the main principle in electrospinning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations